The legitimation of economic and political power in Tonga : a critique of Kauhala ʻuta and Kauhalalalo moieties : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Anthropology at Massey University, Albany - Taliai, 'Opeti Manisela; Taliai, 'Opeti Manisela (Massey University, 2007)
This thesis is a study of the legitimation of economic and political power in Tonga as a critique of Kauhala'uta and Kauhalalalo social moieties. It adopts a socio-historical method of approach but logical considerations inform every aspect of the analysis. This is done in the conviction that logic and fact do not clash but converge and concur at every point such that when they clash we should take it as a sign that either our logical theory needs revision or our observation of the actual process has been amiss. In this, I follow the main lines of the critique of illusions, romanticism, and personalism developed in the philosophical realism of John Anderson. As the central issue of my thesis is legitimation, I have asked whether the evidence and logic square with each other. First, whether the development of legitimation language is later than the social facts, for example, later than the power which the language is designed to legitimate, as seems to be the implication in the relevant literature, or, second, whether the legitimation language has an origin different from that of the social reality it is usually associated with. I have chosen to begin with a brief introductory history of Tongan society based on my interpretation of the origin myth of the first local putative Tu'i Tonga "King of Tonga". The myth introduces the fact that the history of Tonga is what the senior chiefs say. This is shown in the myth through the household advice given to the local Tu'i Tonga by his Samoan older half brothers, Faleua and Falefaa, on how to rule. But, this household advice is just the inverse of an actual event recounted in the myth whereby the younger local Tu'i Tonga is murdered by his senior half brothers. So, the myth, then, is about committing a wrongdoing which leads to a socio-political reformation. Household advice in practice is murdering, so as to build a new nation. To illustrate this new nation building process, I take into consideration the works of the 19th Tu'iKanokupolu, King George Taufa'aahau Tupou\ (~1797-1893), and the 21st Tu'i Kanokupolu, Queen Salote Mafile'o Pilolevu Tupou III (1900-1965), showing a Tu'i Kanokupolu implosion of his senior Tu'i Tonga and Tu'i Ha'atakalaua power. The main indication of this implosion is the replacement of the senior Tu'i Tonga household advisory system with the nineteenth-twentieth century Tupou dynasty's manipulated written history. King George Taufa'aahau Tupou I, the subject of chapter 2, presented his written version with the introduction of his 1875 Constitution. Similarly, in chapter 3, Queen Salote Tupou III reinforced her great, great grandfather's Constitutional principles in her confused lau 'eiki and fie 'eiki styles of genealogical poetry. The theme, of course, promoted in this thesis, is a historical study of the struggle for power, in various forms of dualism, between the Tu'i Tonga and his people on top and the Tu'i Kanokupoiu and their people below. The situation, as always many-to-one, has been perpetuated by the synthesizing universal role of moiety division in constantly igniting the perilous conflict of interests between the two.
Keywords: Tongan politics; Tongan society